The Multimodal Analysis of Mask Images of COVID-19 Comics on Instagram - Henny Merizawati; Nadia Eka Firnanda (English Education Study Program Faculty of Teacher Training and Education, 2022)
This research aims to find images related to masks from social media during the COVID-19 pandemic. The data were gathered by collecting comic pictures from three Instagram accounts: Evacomics, Ahviavia, and Weimankow. The samples of the data contained 18 (Eighteen) mask pictures. This research used Kress and Leeuwen's social semiotic approach, and the data were analyzed using Kress and Leeuwen's Multimodal analysis and Halliday's Systemic Functional Linguistics (SFL): ideational, interpersonal and textual forms. The findings showed that verbal and visual interpretation of mask images contains messages of health protocols for preventing COVID-19. In conclusion, people, including comic makers, can support the government program in promoting health protocols in the pandemic era.